A comparison of subtraction MRI with the standard contrast-enhanced imaging in Perthes' disease. (February 2019) - Jamil, K.; Walker, T.; Onikul, E.; Munns, C. F.; Little, D. G.
Abstract: Purpose: Perthes' disease (PD) results from loss of blood supply to the hip and can progress to femoral head deformity. MRI in the early course of the disease can provide data on the initial extent of infarct. Vascularity of the femoral head is assessed by gadolinium-enhanced MRI (contrast MRI), which may be improved by the digital subtraction technique (subtraction MRI). We hypothesized that gadolinium-enhanced MRI without subtraction was comparable with subtraction MRI in depicting the femoral head perfusion. Methods: In all, 34 patients (34 hips) with unilateral PD had gadolinium-enhanced MRI as part of a prospectively randomized study. Nine patients had three MRIs, 15 had two and ten had a single MRI. Measurement of perfusion of the femoral head (MRI perfusion index) was obtained using digital image analysis on all the MRIs, including both before and after subtraction. A paired sample t-test was performed to compare the measurements. Results: The mean age of the patients was 8.9 years (sd 1.6). At the time of diagnosis, the subtraction MRI did not elicit a statistically significant difference in MRI perfusion index measurements when compared with the contrast MRI (p = 0.19). The same findings were found when including all patients at various stages of the disease (p = 0.30). Qualitatively, although some subtraction MRI images showed superior delineation of epiphysis, there are no significant differences throughout the whole series. Conclusion: Although the current literature supports the increasing role of the subtraction MRI for PD management, our study proposed that the contrast MRI without subtraction technique appears adequate in assessing femoral head perfusion. Level of Evidence: Level I - Diagnostic study